2017
DOI: 10.1051/shsconf/20173600012
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Review on Company Specific Determinants for Sustainability Reporting in United Kingdom (UK) and Malaysia

Abstract: This study aims to comparatively assess the effects of company-specific variables on the level of corporate social responsibility (CSR) information disclosed in publicly-traded companies from United Kingdom (UK) and Malaysia. Content analysis was applied to sampled reports from the FTSE 100 Index and FTSE Bursa KLCI against inferred meanings from the Global Reporting Initiative (GRI)-derived coding base to identify similarities and/or differences in CSR disclosure practices. The Spearman's correlation coeffici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 37 publications
3
8
0
1
Order By: Relevance
“…Social issues dominate firms' annual report disclosures. Overall, the results support Dagiliene and Mykolaitiene (2015), Krivacic (2017) and Tong (2017) who find that CSR disclosure in social issues is higher than in economic or environmental issues.…”
Section: The Extent Of Mandatory Csr Disclosure In Annual Reportssupporting
confidence: 78%
See 1 more Smart Citation
“…Social issues dominate firms' annual report disclosures. Overall, the results support Dagiliene and Mykolaitiene (2015), Krivacic (2017) and Tong (2017) who find that CSR disclosure in social issues is higher than in economic or environmental issues.…”
Section: The Extent Of Mandatory Csr Disclosure In Annual Reportssupporting
confidence: 78%
“…This study refers to Tong's (2017) study in selecting keywords. Tong (2017) uses the G4 issued by GRI for the analysis. Table II displays the keywords used in this study.…”
Section: Methodsmentioning
confidence: 99%
“…The legitimacy theory perceives that corporate characteristics, such as firm size, industry type, and assurance statement practices influence sustainability reporting. Previous studies have found a positive relationship between firm size and the level of environmental, CSR, and sustainability disclosures (Siregar & Bachtiar, 2010;Artiach & Walker, 2010;Kuzey & Uyar, 2016;Kilic & Kuzey, 2017;Tong, 2017;Ali Sahboun, 2017). According to Siregar and Bachtiar (2010), the larger the size of a company, the larger the public attention, and visibility they receive.…”
Section: Theoretical Framework and Hypothesis Development Legitimacy ...mentioning
confidence: 94%
“…His findings were consistent with prior studies that proved the explanatory factor of company size as a consistent predictor for CSR and sustainability disclosures in both developed and developing countries. It is argued that large companies tend to receive much pressure from stakeholders on CSR and sustainability disclosures to improve corporate legitimacy and maintain a good image and reputation (Tong, 2017).…”
Section: Firm Size and Sustainability Reporting Disclosurementioning
confidence: 99%
“…In 2007, the Malaysian Government identified four main areas of CSR disclosure (including the environment, workplace, community and marketplace) to monitor Bursa Malaysia listed companies. Although there are some CSR studies on Malaysia, most of them focus on various aspects of CSR reporting (Ismail et al, 2015;Tong, 2017;Anuforo et al, 2018). Sustainable development in Singapore, however, still has some way to go.…”
Section: Introductionmentioning
confidence: 99%